ANALISIS FAKTOR-FAKTOR YANG MENINGKATKAN KEPERCAYAAN PELANGGAN MELAKUKAN ONLINE SHOPPING DAN DAMPAKNYA TERHADAP MINAT BELI (Studi pada Mahasiswa di Universitas Muhammadiyah Tangerang) - Tarto Tarto; Yanthi Meitry Gunawan (Universitas Muhammadiyah Tangerang, 2019)
The purpose of this study is to analyze how much influence internet technology knowledge, company quality and website quality on customer trust and its impact on buying interest in University of Muhammadiyah Tangerang students. The research sample was 98 students at the Muhammadiyah University of Tangerang. The sampling technique used convenience sampling. Data collection by distributing questionnaires. The method used in this study is the verification method to determine the effect of knowledge of internet technology, company quality and website quality on customer trust and its impact on buying interest in University of Muhammadiyah Tangerang students. The research sample was 98 students at the Muhammadiyah University of Tangerang. The test statistics used are designing structural models, designing measurement models, building path diagrams, testing the appropriate models. Suitability test of structural models and hypotheses using SmartPLS 3.0 software. The results showed that internet technology knowledge, company quality and website quality have a significant influence on customer trust. And customer trust has a significant influence on buying interest.Keyword: internet technology knowledge, company quality, website quality, customer trust, buying interest..